Contextually Differentiated Quality Management for Advanced-Track Learning: A Multi-Site Study in Indonesian State Islamic Senior Secondary Schools - Misini; Patimah, Siti; Murtafiah, Nurul Hidayati; Refliyanto (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2026)
Advanced-track programmes in Indonesian Islamic senior secondary schools are often assessed through enrolment selectivity or visible achievement, while the quality-management processes that make learning meaningful remain underexamined. This multi-site qualitative study analyzes how three State Islamic Senior Secondary Schools in Lampung Province manage quality and learning innovation in advanced-track programmes. Data from the original field study were generated over approximately one academic year through participant observation, in-depth interviews with programme stakeholders, and document analysis. The analysis identifies a shared Plan–Do–Check–Act logic but three contextual profiles: integrative–comprehensive at State Islamic Senior Secondary School 1 Bandar Lampung, academically competitive at State Islamic Senior Secondary School 1 Metro, and academically–spiritually integrated at State Islamic Senior Secondary School 1 Central Lampung. Across cases, quality was enacted through capability mapping, differentiated curriculum pathways, inquiry- and project-oriented learning, digital and laboratory resources, enrichment time, and iterative monitoring. The study proposes the Contextually Integrated Advanced-Track Quality Management model, which adds an equity guardrail to prevent advanced-track provision from becoming a mechanism of fixed student hierarchy. The model contributes to Islamic educational management by linking pedagogical innovation, local institutional identity, inclusive quality education, and continuous improvement.